Short-term moderate intensive high volume training program provides aerobic endurance benefit in wheelchair basketball - Skucas, K.; Pokvytyte, V. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: The aim of this paper was to investigate the effect of short-term period, moderate intensity and high volume endurance training on physiological variables in elite wheelchair basketball players.